Effects of growth regulators on fruiting of tomato cultivar "Miguel Pereira" - Castro, Paulo R. C.; Malavolta, Eurípedes (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1976)
To study the influence on fruiting, (2-chloroethyl) trimethylammonium chloride (CCC) at concentration of 2,000 ppm, succinic acid-2,2-dimethylhydrazide (SADH) (3,000 ppm), gibberellic acid (GA) (200 ppm), and (2-chloroethyl) phosphonic acid (CEPA) (200 ppm) were applied. Treatments with CCC, CEPA, GA and SADH did not affect the total weight of tomato fruits. The growth regulators did not promote changes in fruit number. Applications of CCC and CEPA did not affect the fruit weight average; however, spraying with SADH and GA reduced the fruit weight average.